A trianoni északi határszakasz redemarkálása az 1947. évi párizsi békeszerződés szerint - Suba, János (Közép-Európai Közlemények, 2010)
One of the regulations of the Peace Treaty was the restoration of the confines of the country in atheir original state. The tracing of the border-line, however, as a concequence of the military events and/or the phenomena of nature, has been demolished in several places during the Second World War. In the north the Pozsony (Bratislava) bridge-head was to be abandoned to Czechoslovakia; this meant marking out a new border-line in 6750 m length and the border-line between Austria and Hungary became shorter. On the Hungarian–Czecho-slovakian border the original line of the confines had to be modified at 13 sections and the new border-line became fixed by the agreement of 13 July 1953. In connection with the new agreement 11.5783 – 11.5783 hectares of land changed hands between the two countries at par. The new Hungarian-Soviet boundary was marked, too and the border-line became 136.7 km long, slightly shorter than before. With some lesser or greater modifications the other border-sections became restored as well. The Hungarian–Yugoslavian boundary got shorter just like the ones mentioned before.